Fabrication and investigation of 3D tuned PEG/PEDOT: PSS treated conductive and durable cotton fabric for superior electrical conductivity and flexible electromagnetic interference shielding. (8th September 2019) - Ghosh, Sabyasachi; Ganguly, Sayan; Remanan, Sanjay; Das, Narayan Ch
Abstract: Promotions of conducting e-textiles are drawing attention for mitigating electromagnetic radiation pollution. Probably it is a huge challenge to gain long-term durable and stable fabric for all-weather outdoor application. In this work, a facile dip coating design has been adopted to fabricate PEG/PEDOT: PSS treated fabric. The high electrical conductivity of 51.0 S cm −1 and EMI SE of 46.8 dB (in X-band) were achieved by only 20 dipping cycles (thickness ∼ 0.38 mm), whereas the optimum conductivity and shielding were found to be 82.7 S cm −1 and 65.6 dB at 25 dipping cycles. According to the AFM, XPS, SAXS and FTIR characterization, the enhancement in electrical conductivity was found to be the phase separation between PEDOT and PSS followed by the charge screening phenomena. The exclusive "void-filler" inclusion in the whole fabric also has been evaluated in order to correlate their microstructure (both 2D and 3D) along with the desirable conducting features. Remarkably, the conducting network remains flexible even after prolonged sunlight exposure, thermal air ageing, repeated bending with twisting, peeling with single sided tape, boiling with water, and different organic solvents which proves its versatile mechanical and chemical robustness. Such long term deformations exhibit above 95% retention of EMI SE which offers a promising approach to fabricate a futuristic e-textiles which can address long-term exposure towards the extreme environmental conditions (both wet and dry media).